2018
DOI: 10.1177/0898756418755339
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Dental Cements

Abstract: This review provides an in-depth comparison of advantages and disadvantages of different types of dental cements as they are used for cementing base metal alloy crowns in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…Zinc phosphate cement has no chemical bond to dental structures and has medium compressive strength (62 to 101 MPa), low tensile strength (5 to 7 MPa), and high solubility (0.36%). After mixing, its pH is low, and about 2 and after 24 hours, it reaches 5.5 [62,63]. Despite the low pH of this cement, it has been reported that it has no irritating effect on the pulp and it is biocompatible [64].…”
Section: Semipermanent Cementsmentioning
confidence: 99%
“…Zinc phosphate cement has no chemical bond to dental structures and has medium compressive strength (62 to 101 MPa), low tensile strength (5 to 7 MPa), and high solubility (0.36%). After mixing, its pH is low, and about 2 and after 24 hours, it reaches 5.5 [62,63]. Despite the low pH of this cement, it has been reported that it has no irritating effect on the pulp and it is biocompatible [64].…”
Section: Semipermanent Cementsmentioning
confidence: 99%
“…At the margin of the preparation, dental cement is in constant contact with saliva, a fluid containing a spectrum of proteins with different antimicrobial characteristics dissolved in water (3,4). Good dental cement must be resistant to disintegration and dissolution where a thin layer of cement may possibly be completely dissolved, creating a space susceptible to plaque accumulation and secondary caries, which, if not observed in time, leads to tooth decay, infraction of the margin of restoration, and debonding of the restoration (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have pointed out that water may contribute to the failure of adhesive to bond with dentin (5,(9)(10)(11)(12). Solubility is therefore an im-Stomatology portant feature in the assessment of the clinical durability of dental cements, and has been the subject of numerous experimental and clinical studies (6,(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, improvements in cement properties such as strength, wear resistance, marginal integrity, and esthetics have increased the use of indirect restorations (1). The main factors determining the retention and resistance of indirect crowns include (a) total occlusal convergence, (b) surface area and height, (c) surface finish or roughness, (d) intracoronal auxiliary features of preparation, (e) relative adaptation of the restoration to the abutment, (f) texture of the internal surface of the casting, (g) splinting of multiple units, (h) strength properties of the cast metal super-structure, (i) type of cement, (j) use of venting or internal casting relief, (k) variations in cement viscosity, and variations in the seating forces (1,2). Part of the clinical success of indirect restorations is related to the type of cement that is used for retention.…”
Section: Introductionmentioning
confidence: 99%
“…Resin cements were introduced to overcome the weaknesses of the conventional cements with benefits such as optimal esthetics, favorable mechanical properties, dimensional stability, micromechanical adhesion, minimal solubility, and optimal biocompatibility (9,12). Resin cements can provide a strong bond between the tooth structure and restorative materials (1). Resin cements have greater marginal integrity than glass-ionomer cements.…”
Section: Introductionmentioning
confidence: 99%